I'm sick? I don't train!" - Relation between training during upper respiratory infection and myocarditis - Michał Żuchowski; Dominika Mańdziuk; Patrycja Niewinna; Przemysław Zaroda; Paweł Dąda; Paweł Pawlik; Wojciech Kołodziej; Klaudia Kołodziej; Jakub Wawrzkowicz; Monika Korga (Kazimierz Wielki University, 2024)
Introcudtion Myocarditis is one of the leading causes of sudden cardiac deaths among athletes. One of the factors increasing the risk of this disease is engaging in sports training during an infection. Many athletes, regardless of their level of advancement, are not aware of the risks associated with training during an infection, and those who are aware often ignore them and continue training. Purpose Assessment of behaviors and awareness among runners in Poland regarding the risk of developing myocarditis as a result of training during respiratory tract infections. Material and method In December 2023, a voluntary and anonymous online survey was conducted among a group of 399 adult runners from Poland. The survey included 13 questions, consisting of 11 single-choice questions and 2 multiple-choice questions. Results The percentage of individuals who do not associate training during an infection with an increased risk of myocarditis amounts to as much as 44.4% (n=177), while a staggering 86.7% (n=346) of respondents declare that they undertake training during respiratory infections. Conslusion After analyzing the survey, it's evident that while the Polish running community recognizes the risks of training during infections, many still exercise despite symptoms. Although most understand that intense training and early return to sports can harm health, awareness of myocarditis risks from exertion during infection is lacking. Despite protocols for post-illness return to sports, there's a need for campaigns to educate the running community on infection-related training risks.